2014
DOI: 10.1007/s40292-014-0063-2
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of the Effects of Aerobic Dance Training on Blood Lipids Among Individuals with Hypertension on a Thiazide

Abstract: Although, LDL-C and triglyceride are reduced after aerobic dance training, they were not any more than without it. Aerobic dance training has favorable effects on LDL-C, triglyceride, and systolic and diastolic BP in individuals with hypertension on a thiazide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…Body fat content was reduced in IG only, in line with several other studies using dance as an exercise training intervention [37, 41, 44], but in disagreement with others [45, 47]. In contrast, lean body mass was elevated after intervention in both IG (0.7 kg) and CG (0.4 kg).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Body fat content was reduced in IG only, in line with several other studies using dance as an exercise training intervention [37, 41, 44], but in disagreement with others [45, 47]. In contrast, lean body mass was elevated after intervention in both IG (0.7 kg) and CG (0.4 kg).…”
Section: Discussionsupporting
confidence: 69%
“…A few other studies have applied dancing as an exercise training protocol. For example, dancing with an aerobic component was shown in a RCT to cause positive adaptations in women older than 65 years with arterial hypertension [44]. In addition, Zumba dancing for hospital employees has been demonstrated to decrease the degree of arterial hypertension markedly [37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been widely recommended by both European and American hypertension guidelines that AE can be used as an adjunct to the treatment of hypertension . In previous studies, it has been demonstrated that AE produces the positive effects on systolic blood pressure (SBP) and diastolic blood pressure (DBP) . Furthermore, increasing evidence has indicated that AE has favorable effects on cardiovascular risk factors, cardiac autonomic function, and endothelial pathophysiology in individuals with hypertension .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 24 studies were included in the nal analysis, among which 12 studies were classi ed as progressive aerobic training [23][24][25][26][27][28][29][30][31][32][33][34] and 12 studies were classi ed as nonprogressive aerobic training [35][36][37][38][39][40][41][42][43][44][45][46] . In addition, 4 studies were analyzed twice for presenting two groups of aerobic training 28,31,35 or for performing analyses at two different moments 27 (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…Regarding aerobic training without progression, aerobic exercise groups [35][36][37][38][39][40][41][42][43][44][45][46] were analyzed, of which only two (15.4%)…”
Section: Non-progressive Aerobic Trainingmentioning
confidence: 99%